Commognitive Conflict: How do Critical Thinkers Solve Cognitive Conflict Problems in Geometry? - Satriya Adika Arif Atmaja; Zaenuri; Isnarto; Nuriana Rachmani Dewi (Nino Adhi) (Pendidikan Matematika UNIMOR, 2026)
There has been no research exploring cognitive conflict problems in geometry from commognitive framework. Nevertheless, this framework offers strong potential for gaining new theory about cognitive processes of critical thinkers. This study addresses this gap by exploring in depth how critical thinkers solve cognitive conflict problems in geometry from commognitive framework. Commognitive involves four main components: word use, visual mediators, routines, and narratives. This study employed a qualitative approach to explore the cognitive processes in depth. The instrument used in this study consisted of cognitive conflict problems in geometry designed for junior high school students. The subjects of this study consisted of 17 students from the mathematics olympiad group at Madrasah Tsanawiyah (MTs) Surya Buana Malang, Indonesia. The results revealed two categories: Category A met all critical thinking components and commognitive indicators, whereas Category B met only some. The commognitive conflicts highlighted key moments of cognitive engagement and discourse transformation. These conflicts activated critical thinking components, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. Based on the result, it is recommended that future research explore the development of mathematics instructional designs in cognitive conflict problems based on commognitive framework.